2020
DOI: 10.1177/0266242619884852
|View full text |Cite
|
Sign up to set email alerts
|

There is no need to shout to be heard! The paradoxical nature of corporate social responsibility (CSR) reporting in a Latin American family small and medium-sized enterprise (SME)

Abstract: Drawing on the paradox and reciprocal stewardship theory, this study focuses on tensions in corporate social responsibility (CSR) reporting experienced by a family small and medium-sized enterprise (SME) in a developing Latin American country. Prior literature has suggested a prescriptive, tension-free process, led by family members and driven by an interest to protect and enhance the reputation of both the family and the firm. Relying on an in-depth qualitative approach, this study unveils that CSR reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 111 publications
(195 reference statements)
1
32
0
Order By: Relevance
“…Similarly, the nature of family ties—based on blood ties or legal/cohabiting ties—has an important personal and affective component (Brannon et al., 2013). The integration of theories of stewardship and social exchange can help to explain reciprocation and stewardship behaviour and exchange‐level contributions to social capital (Discua‐Cruz, 2020; Long, 2011; McLarty et al., 2019). Based on the social capital framework, research could investigate the relevance of moral structure, family norms and social interactions as mechanisms influencing women's entrepreneurship.…”
Section: An Integrative View and A Way Forwardmentioning
confidence: 99%
“…Similarly, the nature of family ties—based on blood ties or legal/cohabiting ties—has an important personal and affective component (Brannon et al., 2013). The integration of theories of stewardship and social exchange can help to explain reciprocation and stewardship behaviour and exchange‐level contributions to social capital (Discua‐Cruz, 2020; Long, 2011; McLarty et al., 2019). Based on the social capital framework, research could investigate the relevance of moral structure, family norms and social interactions as mechanisms influencing women's entrepreneurship.…”
Section: An Integrative View and A Way Forwardmentioning
confidence: 99%
“…Similarly, recent studies highlight that a formal way to address stakeholder concerns revolves around formal practices, such as CSR reporting (e.g. Campopiano and De Massis, 2015; Discua Cruz, 2020). Campopiano and De Massis (2015) suggest that the CSR reports of FB tend to focus more on environmental aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Campopiano and De Massis (2015) suggest that the CSR reports of FB tend to focus more on environmental aspects. In Latin America, qualitative studies have revealed that cultural aspects highlight stakeholders as influential in making family firms interested in formally addressing societal concerns based on a balance of both family and business objectives (Discua Cruz, 2020). These studies attribute such attention to a greater concern for protecting relational and social dynamics in the long term (Venturelli et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bosch, on the other hand, as a large, 100% family-owned firm, is considered a predominantly socially responsible player, especially in terms of its supplier management (Kumar & Vaz, 2017 ). In this context, however, it is essential to note that the many good deeds of small and medium-sized family firms making up the majority of the world’s business population stay unnoticed by the general public, as these firms tend not to publicize their good deeds (see, e.g., Déniz & Suárez, 2005 ; Discua Cruz, 2020 ; Niehm et al, 2008 ; Peake et al, 2017 ; Uhlaner et al, 2004 ). Given the severe social and environmental problems our world faces, it is crucial to understand what does or will motivate this group of firms to engage in CSR.…”
Section: Introductionmentioning
confidence: 99%